Synthesis and biological evaluation of 2-arylbenzimidazoles targeting Leishmania donovani. Issue 9 (1st May 2015) - Keurulainen, Leena; Siiskonen, Antti; Nasereddin, Abedelmajeed; Kopelyanskiy, Dmitry; Sacerdoti-Sierra, Nina; Leino, Teppo O.; Tammela, Päivi; Yli-Kauhaluoma, Jari; Jaffe, Charles L.; Kiuru, Paula
Graphical abstract: Abstract: A set of56 2-arylbenzimidazoles was designed, synthesized and tested against Leishmania donovani amastigotes. The left- and right-hand side rings of the molecule, as well as the amide linker were modified. Structurally different derivatives were screened on L. donovani axenic amastigotes at concentrations of 5, 15 and 50 μM, and the ten most active derivatives were selected for further testing. 2-Arylbenzimidazole derivative24 was active against L. donovani -infected THP-1 cells showing 46% parasite inhibition at 5 μM.